Pengeluaran Negara untuk Perlindungan Sosial Dalam Tinjauan Ekonomi Islam Telaah APBN 2023 - Marcella Nazmatul Lail; Dhia, Dinar; Rizki Mansis, Ihsan (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Abstract After the Covid-19 Pandemic, the world was faced with economic uncertainties, such as the food and energy crises, soaring commodity prices, inflation, and rising interest rates. These conditions can threaten the economies of countries in the world, like Indonesia. Therefore, Indonesia needs government efforts to maintain the stability of national economic conditions, by using the state budget as a tool for fiscal policy. The field of social protection is one of the focuses of the 2023 State Budget as a safety net for society when economic conditions are not in good condition, as well as a manifestation of achieving the vision and mission of Islam, namely social welfare. This study aims to examine and relate the relevance of state spending for social protection in the 2023 State Budget in the view of Islamic Economics. The method used is library research. The results of the study show that state spending on social protection, especially the Family Hope Program and Pre-Employment Programs, has fulfilled the six rules of state spending in Islam, but the Indonesian government still needs an evaluation of a series of policies on program implementation in order to provide maximum results. Keywords: Budget, Social Protection, State Expenditure Abstrak Setelah Pandemi Covid-19, global dihadapkan ketidakpastian perekonomian, seperti krisis pangan dan energi, pelonjakan harga komoditas, inflasi, dan peningkatan suku bunga. Kondisi berpengaruh terhadap perekonomian negara-negara di dunia, seperti Indonesia. Indonesia membutuhkan upaya pemerintah dalam menjaga stabilitas kondisi ekonomi nasional dengan penggunaan APBN sebagai alat kebijakan fiskal. Bidang perlindungan sosial menjadi salah satu fokus APBN 2023 sebagai jaring pengaman masyarakat apabila kondisi ekonomi tidak dalam keadaan baik, salah satu wujud pencapaian visi misi Islam yaitu kesejahteraan sosial. Penelitian ini bertujuan untuk mengkaji dan menghubungkan relevansi pengeluaran negara untuk perlindungan sosial dalam APBN 2023 dalam pandangan Ekonomi Islam. Metode yang digunakan adalah studi pustaka (library research). Hasil penelitian menunjukkan bahwa pengeluaran negara pada perlindungan sosial, terutama Program Keluarga Harapan dan Pra Kerja telah memenuhi enam kaidah belanja negara dalam Islam, namun pemerintah Indonesia tetap membutuhkan evaluasi dari serangkaian kebijakan pada pelaksanaan program agar memberikan hasil maksimal. Kata kunci: Anggaran, Pengeluaran negara, Perlindungan sosial